2015
DOI: 10.1038/srep08071
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent radiotherapy and weekly chemotherapy of 5-fluorouracil and platinum agents for postoperative locoregional recurrence of oesophageal squamous cell carcinoma

Abstract: The most optimal management for postoperative locoregional recurrence of oesophageal squamous cell carcinoma is still controversial. Several studies have reported the feasibility and efficacy of concurrent chemoradiotherapy (CCRT), mostly with three-weekly or four-weekly schedule of chemotherapy. However, treatment compliance was not quite satisfactory, probably due to treatment-related toxicities. Since CCRT with weekly chemotherapy regimens have demonstrated a favorable toxicity profile as well as promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
4
11
0
Order By: Relevance
“…However, previously noted trial RTOG 8501 [26,27] showed that the 5-year OS of definitive radiotherapy with or without chemotherapy was 26 and 0% (P < 0.001), respectively. Our findings appear consistent with other studies [11][12][13][14][15] and have indicated that CRT correlates with better survival than radiotherapy alone and is well tolerated in patients who developed LRR. Further, it was also unclear whether patients should receive consolidation chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…However, previously noted trial RTOG 8501 [26,27] showed that the 5-year OS of definitive radiotherapy with or without chemotherapy was 26 and 0% (P < 0.001), respectively. Our findings appear consistent with other studies [11][12][13][14][15] and have indicated that CRT correlates with better survival than radiotherapy alone and is well tolerated in patients who developed LRR. Further, it was also unclear whether patients should receive consolidation chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…However, previously noted trial RTOG 8501 [26], [27] showed that the 5-year OS of de nitive radiotherapy with or without chemotherapy was 26% and 0% (P < 0.001), respectively. Our ndings appear consistent with other studies [11]- [15] and have indicated that CRT correlates with better survival than radiotherapy alone and is well tolerated in patients who developed LRR. Further, it was also unclear whether patients should receive consolidation chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous retrospective analysis [11] indicated that most patients develop lymph node recurrence in the supraclavicular (25.8%) and upper mediastinal (44.4%) regions, and those who underwent salvage CRT had signi cantly better survival than those that underwent radiotherapy alone, chemotherapy, or best supportive care. Similar results were found in other studies [12]- [15] . Overall survival (OS) directly depended on failure patterns and corresponding treatment strategies, so prospective clinical trials were necessary for screening of speci c patients to attain survival bene t from the optimal salvage strategy.…”
Section: Introductionsupporting
confidence: 93%
“…Patients treated with radiotherapy combined concurrently with weekly chemotherapy achieved a high ORR and OS, showed quite low toxicities and no treatment-related deaths were observed. Therefore, concurrent chemoradiotherapy regime resulted in a safe and effective salvage treatment in the selected group of cancer patients [60]. Nevertheless, a further prospective trial with a larger sample size will be necessary to achieve concluding results regarding the efficacy of the treatment.…”
Section: Other Combinations Based On 5-fumentioning
confidence: 94%